Job design and knowledge productivity among administrative and diplomatic officers (PTD) / Nur Izzati Yusof, Mohamad Noorman Masrek and Mohamad Noorman Masrek. - Yusof, Nur Izzati; Masrek, Mohamad Noorman; Masrek, Mohamad Noorman (Universiti Teknologi MARA Cawangan Selangor, 2016)
Knowledge productivity, the central theme of this thesis, brings on new challenges in managing the knowledge workers in the 21st century. This thesis was embarked with the purpose to understand the relationship between the job design and knowledge productivity among Administrative and Diplomatic Officers (PTD). The PTD has been regarded as a premier knowledge worker in the Malaysian government. They primarily acts as a think tank in assisting the government in formulating and maintaining the public policies portfolios. In accordance with the rapid transformations in the age of information, the PTD is required to have knowledge and competencies to face the increasing responsibilities and upcoming challenges. Thus, it is the responsibility of the Malaysian Federal Ministries in overseeing the productivity of their knowledge workers. However, as a consequence of the transition towards the knowledge economy, most organizations including the public sectors are dumbfounded on understanding the drivers of productivity. The traditional factors for workers’ productivity such as rewards and incomes have lost its significance. Organizations clearly do not understand on the concept of knowledge productivity and how to make the knowledge more productive for the benefits of their workers and organizational improvements. Accordingly, based on the literature studies, the researcher found that there is lack of studies with regards to knowledge productivity in the context of Malaysia’s public sectors. This has created a big gaps on how to harness the knowledge of the civil servants, particularly the PTD to become more productive. Identifying the factors that influence the PTD’s knowledge productivity could facilitate the public sectors in enhancing their knowledge workers’ competency and innovation. This study employs a quantitative research approach involving 305 PTDs working in 21 Malaysian Federal Ministries in Putrajaya. Preliminary studies were conducted to gain better understanding on the perceptions of knowledge productivity in the public sectors, followed by a survey to validate the developed conceptual framework and testing the formulated hypotheses. Job design characteristics namely task, knowledge, social and work context characteristics were hypnotized to be significantly related to knowledge productivity measured in terms of knowledge creation process and innovation. The statistical analyses findings revealed that all the formulated hypotheses were well-supported. Hence, the Malaysia’s public sectors need to design the jobs of the PTDs more fittingly as it could harness their knowledge activities to be more productive and this leads to ideas in innovating the public services and processes.